Cesta ke zdraví Náměty k implementaci onkologické prevence do výuky výchovy ke zdraví - Slaná Reissmannová, Jitka (Masaryk University Press, 2021)
Title in English: Journey to Health: Suggestions for the implementation of oncological prevention in teaching health education The methodological material "Journey to Health. Suggestions for the implementation of oncological prevention in teaching health education" is focused on the prevention of oncological diseases and it is intended for teachers of upper primary schools for teaching Health Education, eventually Biology. Cancer is nowadays one of the most common diseases. Prevention plays important role in decreasing the incidence of oncological diseases, therefore it is very important that the basic knowledge about prevention of oncological diseases be given to primary school pupils. The main purpose is to acquaint pupils with primary and secondary prevention of oncological diseases and to increase their health literacy in this area. The material includes a suggestion for 20 lessons. Each of them contains professional information for teachers' theoretical preparation, suggestions for the lesson, a worksheet with solutions, and proposal activities on the topic.